The Implementation of Project-Based Learning to Cultivate Discipline and Responsibility Among Sixth-Grade Elementary Students - Muhammad Fazis Musyary; Arief Cahyo Utomo (FKIP - Universitas Riau, 2026)
This study aims to describe the role of teachers in implementing Project Based Learning (PjBL) as a learning strategy to develop discipline and responsibility among sixth-grade elementary school students. This study employed a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving teachers and students during the learning process. The results show that the implementation of PjBL fosters students’ discipline through habits of time management, adherence to rules, maintaining order, and self-regulation in social interactions. In addition, responsibility is developed through active participation in task completion, willingness to acknowledge mistakes, engagement in group work, and social awareness. Structured project activities encourage students to be more active and responsible in learning. This study is limited by its focus on a single school and the use of a qualitative approach that does not measure effects quantitatively. Therefore, future research is recommended to involve broader subjects and combine quantitative methods to examine the effectiveness of PjBL more comprehensively.